2021
DOI: 10.3390/pr9020355
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Enzymatic Biodiesel Production and Commercialization

Abstract: Enzymatic biodiesel production has attracted tremendous interest due to its well-recognized advantages. However, high enzyme costs limit the application of enzymatic processes in industrial production. In the past decade, great improvements have been achieved in the lab and the industrial scale, and the production cost of the enzymatic process has been reduced significantly, which has led to it being economically competitive compared to the chemical process. This review introduces the progress achieved in enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 68 publications
(86 reference statements)
0
31
0
1
Order By: Relevance
“…The most commonly used commercial process for biodiesel production is alkali-catalyzed transesterification using sodium hydroxide or potassium hydroxide due to their relatively low cost and high conversion efficiency [3]. However, chemical transesterification has multiple disadvantages [5], such as the high dependency of conversion efficiency on the content of water and free fatty acids in the raw materials and the tremendous energy consumption due to the high reaction temperature and product separation process. Moreover, the acid or base catalysts are not reusable, and extra steps of neutralization are required to dispose of them as an aqueous salt waste stream, which is less environmentally hazardous [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used commercial process for biodiesel production is alkali-catalyzed transesterification using sodium hydroxide or potassium hydroxide due to their relatively low cost and high conversion efficiency [3]. However, chemical transesterification has multiple disadvantages [5], such as the high dependency of conversion efficiency on the content of water and free fatty acids in the raw materials and the tremendous energy consumption due to the high reaction temperature and product separation process. Moreover, the acid or base catalysts are not reusable, and extra steps of neutralization are required to dispose of them as an aqueous salt waste stream, which is less environmentally hazardous [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, biocatalytic transesterification, which is catalyzed by lipases, has been intensively studied for biodiesel production [5,[7][8][9]. As lipases catalyze the reaction through interactions with the molecules at specific sites, the conversion efficiency and product purity are high, with little need for downstream processing.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, the advantages of enzymatic approach over conventional alkalibased processes have been clearly demonstrated in biodiesel production from non-refined feedstock. The enzymatic approach is less energy intensive, more environment friendly, simplifies the separation of the byproduct glycerol, and eliminates the need for water-washing step that consequently reduce wastewater treatment cost [186,187]. Most importantly however, enzymes are insensitive towards free fatty acids (FFA) content in the feed, allowing it to be used with low quality feedstock.…”
Section: Cost Analysis and Viability Of Immobilized Enzymesmentioning
confidence: 99%
“…They even catalyze the FFA together with the transesterification of the triglycerides, which increases the overall biodiesel yield. Nevertheless, the high cost of enzymes remains the main challenge facing the commercialization of enzymatic biodiesel production processes [187,188]. In an economic study on the production of 1000 tons of biodiesel from palm oil, alkali process was found to be more feasible that enzymatic process, when the enzyme was used in a soluble form [189].…”
Section: Cost Analysis and Viability Of Immobilized Enzymesmentioning
confidence: 99%
“…Biodiesel is a non-toxic and biodegradable liquid fuel composed of long chain fatty acid alkyl esters with short chain alcohols, generally methanol and ethanol [1]. The synthesis of these compounds can be driven by chemical or enzymatic catalysts, and industrial production is usually done by chemical transesterification of triglycerides, generally with alkaline catalysts [2]. However, in this reaction, soaps are produced, especially if the oil used contains free fatty acids, and this secondary reaction reduces biodiesel yields and makes the separation and purification of the products notably difficult [3,4].…”
Section: Introductionmentioning
confidence: 99%